Partial purification and application of a bacteriocin produced by probiotic Lactococcus lactis C15 isolated from raw milk. (1st November 2022) - Lei, Wenping; Hao, Lulu; You, Shanbing; Yao, Hui; Liu, Chengguo; Zhou, Hui
Abstract: Food-borne pathogens pose health challenges to consumers and are serious concerns in the food industry. Accordingly, we investigated the probiotic properties of Lactococcus lactis C15 and the biological properties of the bacteriocin it produces. The results show C15 exhibited strong gastrointestinal tolerance, excellent cell surface properties, high adhesion ability to Caco-2 cells (>90%), and good safety in vitro . The active peptide produced by C15 has inhibitory activity against pathogens, even after exposure to elevated temperatures (60–121 °C) and low pH values (pH 2–5). L. lactis C15 contains the Lactococcin B gene, which produces a nisin-like bacteriocin . Partially purified bacteriocin effectively antagonized the growth of Escherichia coli added to ultra-high temperature instantaneous sterilization (UHT) milk. The inhibition of E. coli was similar to that of the reference bacteriocin (nisin). This research aimed to provide a new strategy for food preservation that avoids traditional chemical preservatives. Highlights: A nisin-like bacteriocin inhibiting both Gram-negative/positive bacteria was isolated. Bacteriocin showed efficacy at different pH, surfactants, and high temperatures. Bacteriocin was identical sequences to Lact B and could inhibit E. coli in UHT milk.